The trust-driven path to consumer engagement behaviors: Exploring the role of streamer and platform characteristics in live-streaming E-commerce - Adi Prasetyo Tedjakusuma; Andri Dayarana K. Silalahi; Ixora Javanisa Eunike; Do Thi Thanh Phuong; Dalianus Riantama (Digital Business)
Live-streaming e-commerce is revolutionizing online retail by fostering real-time consumer engagement, yet limited research explores how streamer and platform characteristics jointly influence trust and drive consumer engagement behaviors (CEB). This study examines how streamer attributes (beauty, humor, passion, expertise, and warmth) and platform features (interactivity and personalization) shape trust in streamers and products, subsequently affecting CEB dimensions, including augmenting, co-developing, influencing, and mobilizing. Using data from 682 respondents and analyzing with Structural Equation Modeling (SEM) via SmartPLS 4.0, the findings reveal that beauty and interactivity are pivotal for trust in streamers, while expertise and personalization are critical for trust in products. Trust in streamers emerged as the strongest predictor of CEB, emphasizing its role in fostering consumer loyalty and interaction. This research contributes to theory by integrating socio-technical perspectives with trust-based consumer engagement frameworks, offering a holistic understanding of trust to cultivate CEB. Practically, the study highlights the importance of employing streamers with strong interpersonal appeal and creating interactive, personalized shopping experiences to boost trust and engagement. The study advances live-streaming e-commerce by providing insights and presenting an original, trust-driven model for enhancing consumer engagement.